Diagnostic Accuracy of Time to First Positivity of Blood Cultures for Predicting Severe Clinical Outcomes in Children with Pneumonia-Related Bacteremia. (October 2020) - Zhang, Yin; Lin, Jilei; Shi, Qingxia; Li, Chulin; Liu, Jingyue; Dai, Jihong
Early recognition of severe clinical outcomes in children with pneumonia-related bacteremia is vitally important because of the high mortality. This study aims to explore risk factors for severe clinical outcomes in children with pneumonia-related bacteremia and evaluate the value of time to first positive blood cultures (TTFP) in predicting prognosis. Children with pneumonia-related bacteremia in Children's Hospital of Chongqing Medical University were included (January 2013-May 2019), respectively. TTFP and clinical parameters were collected and analyzed. The area under the curve (AUC)-receiver operating characteristic was used to evaluate the discrimination ability of TTFP. Multivariate logistic regression tests were performed to evaluate the association between TTFP and severe clinical outcomes. A total of 242 children with pneumonia-related bacteremia were included. The least absolute shrinkage and selection operator (LASSO) regression analysis identified TTFP, serum albumin (ALB) and lactic dehydrogenase (LDH) as predictors of in-hospital mortality. Multivariate logistic regression analysis showed that shorter TTFP (OR 0.94; 95% CI 0.89 to 0.97; p<0.01), lower ALB level (OR 0.93; 95% CI 0.89 to 0.98; p<0.01) and higher LDH level (OR 1.001; 95% CI 1.000 to 1.001; p<0.01) were risk factors for in-hospital mortality in children with pneumonia-related bacteremia. AUC of TTFP for predicting in-hospital mortality was 0.748 (95% CI 0.668 to 0.829). Shorter TTFP (≤16 hours) was associated with in-hospital mortality and septic shock. TTFP plays an important role in predicting severe clinical outcomes in children with pneumonia-related bacteremia.